« La propagande soviétique de 1917 à 1991 : paix et désarmement au service de l’idéologie ? » - Jacques Le Bourgeois (Revue LISA)
From the decree on Peace in 1917 to Gorbatchev’s “Zero option” in 1987, the themes of Peace and then of disarmament, were recurrent and fundamental topics in Soviet propaganda. After Trotsky suggested the idea of peace without arms, from 1918 the USSR quickly came back to a more pragmatic conception by setting up a powerful Red Army which Stalin, as well as his successors, kept reinforcing, while championing the struggle against militarism. Crowned with glory thanks to its victory over Nazism, soon after World War II, the USSR went so far as to promote the set of pacifist themes as a central pillar of its doctrine; it became its universal standard bearer. But even if the theme, generous and idealistic as it might be, mobilized sincere sympathisers, it also gave rise to serious doubts, for it lent itself to ambiguous interpretations. The USSR no longer contented itself with national defence, it was arming itself excessively and was becoming a nuclear superpower. And the “Peace” for which the homonymous movement campaigned was then perceived no longer as a praiseworthy aim but as a concept serving an ideology. Oddly enough it was when the USSR disarmed that the regime collapsed, as if paradoxically Peace and disarmament were incompatible with the doctrine. But without resorting to a shortcut that is furthermore fallacious, we find it interesting to show, thanks to posters of Soviet propaganda and in the light of the historical context, from 1917 to 1991, how the set of themes was instrumentalized, while being at the same time the very essence of a doctrine which presented millenarian aspects. Indeed, the Soviet Peace is not basically of the same nature as the capitalist peace. For some, absolute Peace is a myth, for others, the Peace that is offered is only relative and unacceptable.